2023
DOI: 10.1038/s41598-023-31190-x
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in physical fitness of rural Chinese children and adolescents aged 7–18 years from 1985 to 2019

Abstract: The main purpose of the study was to evaluate the secular trends in physical fitness of Chinese rural children and adolescents aged 7–18 from 1985 to 2019. The speed, muscular strength, explosive power fitness, cardiorespiratory fitness, and flexibility were investigated by National Survey on Students’ Constitution and Health in 1985, 2000, 2010 and 2019. During the period 1985–2000, the physical fitness of Chinese rural children and adolescents improved except for flexibility, and almost all of them reached t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…A study by Wang (2019) indicated that increased paternal education levels reduced the gap in health inequalities between urban and rural children, with the reductions being greater among boys, which may also be a reason. The proportion of fathers (offspring aged 7-18 years) with a junior high school or higher education has increased in China (Li, Zhang et al, 2023). Although more information is not available, data from the 2020 China Population Census showed that the Chinese population with a junior college or higher degree increased from 0.04% in 1964 to 15.47% in 2020 (Office of the Leading Group for the Seventh National Population Census of the State Council, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Wang (2019) indicated that increased paternal education levels reduced the gap in health inequalities between urban and rural children, with the reductions being greater among boys, which may also be a reason. The proportion of fathers (offspring aged 7-18 years) with a junior high school or higher education has increased in China (Li, Zhang et al, 2023). Although more information is not available, data from the 2020 China Population Census showed that the Chinese population with a junior college or higher degree increased from 0.04% in 1964 to 15.47% in 2020 (Office of the Leading Group for the Seventh National Population Census of the State Council, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the prevalence of stunting in urban children and adolescents in China decreased from 8.6% to 1.4% between 1985 and 2014, while it decreased from 24.2% to 3.2% in rural areas (Song et al, 2019). During this period, the Chinese government noted serious nutritional deficiencies in rural areas, and to improve the growth and development of rural children, the state launched the “Nutritional Improvement Program for Rural Compulsory Education Students” in 2011 (Li, Taerken, et al, 2023; Ma et al, 2022). Through this initiative, rural children's diets have changed and their nutritional levels have improved, contributing to an increase in adult height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 That said, fitness trends of children and adolescents from only several high-income countries were reported recently. [27][28][29][30]36,37 Fitness levels, similar to adiposity, can vary significantly across countries and even regions from the same country based on socioeconomic development, so it's important to consider each location's specificities. 36,37 Children and adolescents with lower SES have regularly presented less favourable trends in fitness.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] On the other hand, there is very little data on fitness trends in children living with excess weight especially data that would allow examining the evolution of weight-based disparities over a long period. [26][27][28][29][30] Generally, across several available studies, children and adolescents with overweight and obesity presented with larger decrements in the health-related fitness components (i.e., mostly considering the CRF component) when compared with their peers with normal weight 26,[31][32][33][34][35] with some conflicting results reported. 28 That said, fitness trends of children and adolescents from only several high-income countries were reported recently.…”
Section: Introductionmentioning
confidence: 99%